Implementation of Children’s Sex Education Through Psychoeducational Approaches - Adna Daruesa; Murfiah Dewi Wulandari (Lembaran Ilmu Kependidikan, 2026)
Background - Sex education in elementary schools is often hindered by its sensitive nature, despite the urgent need for children to understand personal boundaries and reproductive health through age-appropriate approaches Purpose - This study aims to examine the implementation of children’s sex education through a psychoeducational approach at Muhammadiyah 16 Elementary School, Surakarta. Method/approach - This research employed a qualitative design, with data collected through observation, documentation, and in-depth interviews involving the school principal, teachers, and students. These techniques were used to obtain comprehensive and in-depth information about the research phenomenon, allowing the researchers to understand the participants’ experiences, perspectives, and the context in which the learning process took place. Findings - The findings reveal that sex education through psychoeducation is implemented by adjusting learning materials to suit children’s developmental stages and by applying interactive and communicative learning methods. This approach enables children to receive information in a manner that is age-appropriate, understandable, and relevant to their daily experiences. The program contributes positively to improving children’s understanding and awareness of reproductive health, personal body boundaries, and the importance of protecting themselves from inappropriate behavior. However, several challenges remain, including limited instructional time, differences in children’s levels of understanding, and the sensitive nature of the subject matter, which requires teachers to deliver the material carefully and appropriately. Conclusions - This study provides empirical insights into the implementation of children’s sex education in elementary school, particularly through psychoeducational approaches that are adapted to students’ developmental stages. It also highlights the practical strategies, benefits, and challenges faced by schools in delivering sensitive reproductive health materials in an age-appropriate and communicative manner. Novelty/Originality/Value - Serve as a reference for the development of more comprehensive and contextually appropriate educational programs in the future.